Dogsledding and Extreme Sports : A Nonfiction Companion to Magic Tree House #26, Balto of the Blue Dawn - Osborne, Mary Pope and Boyce, Natalie Pope (New York Random House, 2016)
"A nonfiction companion to Magic Tree House #54: Balto of the Blue dawn."-
Inlclude Illustration and Index
Keywords: Iditarod (Race) -- Balto (Dog)